Deities in the Mari Texts - Nakata, Ichiro
Complete inventory of all the information on the deities found in the published Old Babylonian cuneiform texts from Mari and analytical and comparative evaluation thereof with regard to the official and popular pantheons of Mari; Submitted in partial fulfilment of the requirements for the Degree of Doctor of Philosophy.